Traditional Beliefs about Weretigers among the Garos of Meghalaya (India) - Francesco Brighenti (eTropic: electronic journal of studies in the tropics, 2017)
The Garos, a tribal group who live in India (western highlands of Meghalaya and the southern foothills of Assam) and northern Bangladesh, are noted for their diverse beliefs on weretigers – that is, human beings with the ability of turning themselves, in various ways, into ferocious tigers and subsequently back to human form. The present paper provides a first attempt at classifying the different motifs in Garo weretiger-lore which include traditional beliefs of: (1) a legendary ‘race’ of monstrous tigermen ruled over by a Tiger Mother; (2) individuals endowed with a ‘dual’ vital principle inhabiting a human body during daytime and a tiger one at nighttime; and (3) shape-shifters who can physically metamorphose into tigers through magical arts. This classification highlights the rich variety of beliefs held by the Garos on these quintessential liminal beings, and provides a critical analysis of the most frequently occurring class of werebeasts in the folktales, legends, and epics of tropical Asia.